The impact of heme biosynthesis regulation on glioma aggressiveness: Correlations with diagnostic molecular markers - Mischkulnig, Mario; Kiesel, Barbara; Rötzer-Pejrimovsky, Thomas; Borkovec, Martin; Lang, Alexandra; Millesi, Matthias; Wadiura, Lisa I.; Hervey-Jumper, Shawn; Penninger, Josef M.; Berger, Mitchel S.; Widhalm, Georg; Erhart, Friedrich (Frontiers in Molecular Neuroscience, 2022)
Background: The prognosis of diffusely infiltrating glioma patients is dismal but varies greatly between individuals. While characterization of gliomas primarily relied on histopathological features, molecular markers increasingly gained importance and play a key role in the recently published 5th edition of the World Health Organization (WHO) classification. Heme biosynthesis represents a crucial pathway due to its paramount importance in oxygen transport, energy production and drug metabolism. Recently, we described a “heme biosynthesis mRNA expression signature” that correlates with histopathological glioma grade and survival. The aim of the current study was to correlate this heme biosynthesis mRNA expression signature with diagnostic molecular markers and investigate its continued prognostic relevance. Methods: In this study, patient data were derived from the “The Cancer Genome Atlas”(TCGA) lower-grade glioma and glioblastoma cohorts. We identified diffusely infiltrating gliomas correlating molecular tumor diagnosis according to the most recent WHO classification with heme biosynthesis mRNA expression. The following molecular markers were analyzed: EGFR amplification, TERT promoter mutation, CDKN2A/B homozygous loss, chromosome 7+/10- aneuploidy, MGMT methylation, IDH mutation, ATRX loss, p53 mutation and 1p19q codeletion. Subsequently, we calculated the heme biosynthesis mRNA expression signature for correlation with distinct molecular glioma markers/molecular subgroups and performed survival analyses. Results: A total of 649 patients with available data on up-to-date molecular markers and heme biosynthesis mRNA expression were included. According to analysis of individual molecular markers, we found a significantly higher heme biosynthesis mRNA expression signature in gliomas with IDH wildtype (p<0.0005), without 1p19q codeletion (p<0.0005), with homozygous CDKN2A/B loss (p<0.0005) and with EGFR amplification (p=0.001). Furthermore, we observed that the heme biosynthesis mRNA expression signature increased with molecular subgroup aggressiveness (p<0.0005), being lowest in WHO grade 2 oligodendrogliomas and highest in WHO grade 4 glioblastomas. Finally, the heme biosynthesis mRNA expression signature was a statistically significant survival predictor after multivariate correction for all molecular markers (p<0.0005). Conclusion: Our data demonstrate a significant correlation between heme biosynthesis regulation and diagnostic molecular markers and a prognostic relevance independent of these established markers. Consequently, heme biosynthesis expression is a promising biomarker for glioma aggressiveness and might constitute a potential target for novel therapeutic approaches.